Description of a Housekeeping Program as One of the Occupational Safety and Health Programs at Petrochemical Company - Rr Sri Rejeki Eviyanti Puspita Sari; Hilmy Ishar Ikhsani (The Indonesian Journal of Occupational Safety and Health, 2021)
Introduction: Non-fatal accidents are estimated to occur in 374 million cases each year and have serious consequences for the productivity of workers. Petrochemical Company, which is a company that operates in the field of fertilizers and other chemicals, needs to conduct an Occupational Safety and Health (OSH) program, one of which is the Housekeeping program. The purpose of this study is to determine the housekeeping program at Petrochemical Company and the application at Amurea II Plant III of Petrochemical Company. Methods: This research was conducted at Petrochemical Company in June 2017. This study used a cross-sectional design. The variables use were the OSH policy, the housekeeping program, the housekeeping procedures, and the applications of housekeeping. The primary data were obtained through direct observation and the secondary data were obtained from the company’s documents. Results: Petrochemical Company has included the housekeeping program in the OSH policy. There are two housekeeping programs at Petrochemical Company, namely daily housekeeping and monthly housekeeping. Also, there are 2 types of procedures in the housekeeping program, namely units that can do the housekeeping program and units that cannot do the housekeeping program. Moreover, the housekeeping program has been implemented in all units, one of which is at Amurea II Plant III Project. Conclusion: The Housekeeping program has been integrated in the company’s policy so that the housekeeping program can be done by all workers both daily and monthly. Housekeeping application has also been implemented at Amurea II Plant III of Petrochemical Company. Keywords: housekeeping procedure, housekeeping program, occupational safety and health policy